Phyloepigenomic comparison of great apes reveals a correlation between somatic and germline methylation states - Martin, David I.K.; Singer, Meromit; Dhahbi, Joseph; Mao, Guanxiong; Zhang, Lu; Schroth, Gary P.; Pachter, Lior; Boffelli, Dario (Genome Research, 2011)
We have determined methylation state differences in the epigenomes of uncultured cells purified from human, chimpanzee, and orangutan, using digestion with a methylation-sensitive enzyme, deep sequencing, and computational analysis of the sequence data. The methylomes show a high degree of conservation, but the methylation states of ∼10% of CpG island-like regions differ significantly between human and chimp. The differences are not associated with changes in CG content and recapitulate the known phylogenetic relationship of the three species, indicating that they are stably maintained within each species. Inferences about the relationship between somatic and germline methylation states can be made by an analysis of CG decay, derived from methylation and sequence data. This indicates that somatic methylation states are highly related to germline states and that the methylation differences between human and chimp have occurred in the germline. These results provide evidence for epigenetic changes that occur in the germline and distinguish closely related species and suggest that germline epigenetic states might constrain somatic states.